Australian news media reporting of methamphetamine: an analysis of print media 2014–2016. (26th October 2020) - Rawstorne, Patrick; O'Connor, Rosslyn; Cohn, Amanda; Fredrickson, Anne; Jayasinha, Ranmalie; Hayen, Andrew; Lancaster, Kari; Nathan, Sally
Abstract: Objectives : To examine the representation and framing in Australian print media of methamphetamine and methamphetamine users from 2014 to 2016 when media attention was heightened around the National Ice Taskforce, including the implications of the coverage and framing in limiting public health responses to the problem. Methods : A quantitative media content analysis examined media portrayals of methamphetamine, including crystalline methamphetamine (also referred to by other names including 'crystal' or 'ice'), in 1, 364 Australian print media articles published 2014–2016. Results : The largest number of articles about methamphetamine were published in 2015 with a higher proportion of these articles framed as a crisis than in other years. A crisis framing predominated media reporting across all years, with crime and legal consequences a key focus. Users were positioned predominantly as criminals, deviants or addicts. Conclusions : The coverage of methamphetamine in the Australian print media mostly serves to construct methamphetamine use as an urgent social problem, often framed from a legal perspective and associated with violent, dangerous, deviant and aggressive users. Implications for public health : Such reporting and stigmatisation of methamphetamine use can undermine public health policy responses and strategies, including early intervention and treatment and focused efforts directed at those most at risk of harm.